2014
DOI: 10.1111/ajfs.12073
|View full text |Cite
|
Sign up to set email alerts
|

Investor Sentiment, Product Features, and Advertising Investment Sensitivities

Abstract: Investor sentiment plays an important role, affecting firm level advertising expenditures. We provide evidence that financially constrained firms exhibit lower advertising investment-cash flow sensitivity and higher advertising investment-q sensitivity during high sentiment periods. The patterns are driven mainly by those firms facing financial constraints. More importantly, we identify several product features that also affect advertising investment sensitivities. Sorting on product features generates investm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…In addition, local firms experiencing financial constraints reduce commercial product innovations (Gorodnichenko and Schnitzer 2013), which is related to the product-in-marketing strategy. Luo, Jiang, and Cai (2015) found a negative relationship between financially constrained firms and advertising–cash flow sensitivity during investors’ high-sentiment periods. Finally, other evidence shows that financial constraints negatively affect exports in SMEs (Jinjarak and Wignaraja 2016) and intangible investments that include marketing intensity (Mishra and Ewing 2020).…”
Section: Proposed Conceptual Frameworkmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, local firms experiencing financial constraints reduce commercial product innovations (Gorodnichenko and Schnitzer 2013), which is related to the product-in-marketing strategy. Luo, Jiang, and Cai (2015) found a negative relationship between financially constrained firms and advertising–cash flow sensitivity during investors’ high-sentiment periods. Finally, other evidence shows that financial constraints negatively affect exports in SMEs (Jinjarak and Wignaraja 2016) and intangible investments that include marketing intensity (Mishra and Ewing 2020).…”
Section: Proposed Conceptual Frameworkmentioning
confidence: 95%
“…Although the references do not exhibit a direct relation between financial constraints and marketing intensity, they are related in some way to marketing intensity efforts. In this situation, there exists a negative impact on advertisement spending (Fee, Hadlock, and Pierce 2009), product innovation (Gorodnichenko and Schnitzer 2013), advertising–cash flow sensitivity (Luo, Jiang, and Cai 2015, small and medium enterprise (SME) exports (Jinjarak and Wignaraja 2016), and intangible investments (Mishra and Ewing 2020).…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%
“…The affordability argument would, therefore, suggest that periods of high sentiment are associated with higher expenditure on advertising. The converse would be true for low sentiment periods, when firms are short of funds and are forced to curtail their advertising budgets (Joseph & Richardson, 2002;Luo et al, 2014;Tellis, 1998).…”
Section: Investor Sentiment and Advertising Expenditurementioning
confidence: 99%
“…They systematically underestimate the expected cash flows and/or overestimate risk, causing an undervaluation of stocks. This undervaluation and investors' heightened aversion to risk make it difficult for managers to obtain new funds from investors (Luo, Jiang, & Cai, 2014). This is especially true for financially constrained firms-that is, firms that have low or negative internal cash flows and face substantial uncertainty about their future prospectswhose access to external finances may dry up dramatically during low sentiment periods.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Luo et al (2014) found that durable goods rely less on advertising than non-durable goods. In general, durable goods face higher switching costs than non-durable goods.…”
Section: Introductionmentioning
confidence: 99%